UTILIZATION OF INTERNET MEDIA BY FISHERIES EXTENSION AGENTS IN THE ROKAN HILIR REGENCY OF RIAU PROVINCE - Damanik, Hengky; Hendri, Ridar; Kusai, Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted from January until February 2019 in the Rokan Hilir district of Riau Province. The purpose of this research was to determine the extent to which internet media utilization was carried out by fisheries extension workers in the Rokan Hilir Regency Riau Province. This research uses census method then analyzed using qualitative method. The results of this research indicate that fisheries extension workers in the Rokan Hilir Regency are highly utilizing the internet as a medium for conducting conselling. Key words : Fisheries Extension Agent, Cyber Extension